Preparation Of Nitrogen Containing Hydrochar By Hydrothermal Carbonization Of Water Spinach And Soy Bean Sprout Waste - Mohd, Nurul Syazliza (Universiti Sains Malaysia, 2018)
Hydrothermal carbonization (HTC) is a thermochemical pre-treatment process where solid biomass is treated under hot compressed water to produce carbonaceous material called hydrochar which is coal-water slurry state. Hydrochar is one of alternatives in replacing coal which takes hundred to million years to be formed while hydrochar only require less than 12 hours to produce. Water spinach and soy bean sprouts are selected as the feedstock in this research because of their higher production potential in Malaysia can be easily attain as Malaysian dishes always contain both of these type of vegetables. In this study, hydrothermal carbonization was done from 180oC to 200oC for 2 to 6 hours residence time. Raw feedstock was fed into hydrothermal carbonization at heating rate of 25oC/min. The product obtained was filtered and dried in oven at 105oC for one day, forming hydrochar. The best conditions that producing the highest yield of hydrochar was 180oC and 6 hour of residence time which producing 44.60% hydrochar yield. Water spinach waste was producing higher hydrochar yield than soy-bean sprout waste which are 44.60% and 40.80% respectively for the highest yield obtained. The hydrochars were characterized using scanning electron microscope (SEM), energy- disperse x-ray (EDX) and fourier-transform infrared spectroscopy (FTIR) that shows the hydrochars properties. The results revealed that water spinach and soy-bean sprout waste were potential source for preparation of hydrochar by hydrothermal carbonization.